PELAKSANAAN DOKUMENTASI ASUHAN KEPERAWATAN DI TEMPAT PRAKTIK MANDIRI PERAWAT - Astutik, Emi Eliya Eliya; Purwaningrum, Yuniasih; Yuwanto, Mahmud Ady; Budiman, M.Elyas Arif (NHM PRESS, 2024)
Actions carried out by nurses with nursing care can be recorded and proven through documentation of nursing care. Documenting nursing care is very important not only for nurses who provide nursing care in hospitals, health centers but also in independent practice settings. The aim of this research is to analyze factors in documenting nursing care in nurses' independent practice settings. This research design uses a correlational design with a cross sectional approach. The population of this study was 175 respondents and the sample was taken from 63 respondents using purposive sampling technique. This research test uses the Spearman Rank test. The results of the research show that there is a relationship between knowledge and motivation and documentation of nursing care in the nurse's independent practice setting with p value (0.000) < (0.005) with a correlation coefficient of 0.571, including the strong category. The better the nurse's knowledge and the higher the nurse's motivation, the better complete documentation of nursing care.